Pengaruh Lama Penyimpanan Pada Suhu Kamar Telur Itik Segar Dan Telur Yang Mengalami Pengasinan Ditinjau Dari Jumlah E coli ( EFFECT OF LONG STORAGE IN THE ROOM TEMPERATURE FRESH DUCK EGGS AND DUCK EGGS IN SALTING PROCESS VIEWED FROM TOTAL OF E. coli - Finata, Ratna Pandu; Rudyanto, Mas Djoko; Suarjana, I Gusti Ketut (Buletin Veteriner Udayana; Vol. 7 No. 1 Pebruari 2015, 2015)
This study aims to determine the number of bacteria Escherichia coli (E. coli) in fresh eggsand eggs in the salting process that is derived from UKM Mulyo, Mojokerto. A total of 24 day-oldduck eggs for the treatment of 12 fresh eggs and 12 eggs salting process. Examination of E. coli onthe first day, to eight, to 15, and day 22. Inspection is done by planting in the media EosinMethylene Blue Agar (EMBA). The results showed that the amount of E. coli on fresh eggs andegg salting increased on the first day until the eighth day, whereas on day 15 to day 22 decreased.Kesimpulanya that the amount of E. coli bacteria in fresh eggs and egg in the process pengasian increase until the eighth day and decreased on day 22.
Keywords: duck eggs, Escherichia coli, EMBA media